Therapeutic Potential of an Anti-PLAC1 Antibody-Drug Conjugate in a Mouse Model of Human Breast Cancer - Mahmoudian, Jafar; Ghods, Roya; Jeddi-Tehrani, Mahmood; Ghaffari-Tabrizi-Wizsy, Nassim; Nejadmoghaddam, Mohammad Reza; Ghahremanzadeh, Ramin; Ostad, Seyed Nasser; Zarnani, Amir-Hassan (Iranian journal of immunology, 2025)
Background:Placenta-specific 1 (PLAC1) is an oncoplacental genes aberrantly expressed in various malignancies. Antibody-drug conjugates (ADC) offer a promising therapeutic approach by enhancing efficacy and reducing toxicity of treatment compared to cytotoxic small-molecule agents. Objective: To evaluate the efficacy of an SN38-conjugated monoclonal anti-PLAC1 antibody in a mouse model of breast cancer. Methods: Anti-human PLAC1 monoclonal antibodies were generated and characterized. SN38 was conjugated to an anti-PLAC1 antibody (clone: 2H12C12) and conjugation efficacy was determined by UV spectrophotometry. The antigen-binding activity of the conjugated antibody was assessed using ELISA and flow cytometry. In vitro , the cytotoxic profile of 2H12C12-SN38 was evaluated in MDA-MB-231 breast cancer cells using a fluoroimetric viability assay. The impact of 2H12C12-SN38 on MDA-MB-231 tumor growth and angiogenesis ex vivo was examined using chorioallantoic membrane (CAM) assay followed by immunohistochemical analysis. Pharmacokinetics of 2H12C12-SN38 in mice was determined by serial venipuncture following ADC administration. The inhibitory effects of anti-PLAC1 ADC on tumor growth were evaluated in a nude mouse xenograft model of human breast cancer. Results: The anti-PLAC1 ADC exhibited a substantial cytotoxicity against MDA-MB-231 cells, with effects observed at concentration as low as ~33 nM. In the CAM assay, the ADC significantly reduced the growth of MDA-MB-231 tumor but did not produce a significant effect on tumor angiogenesis. Pharmacokinetic analysis in mice demonstrated an average half-life (t1/2) of approximately 80 hours. In a nude mouse xenograft model, treatment with the ADC resulted in a significant reduction in tumor size compared with isotype-matched antibody-SN38 conjugate, or free SN38. Conclusion:This study represents the first therapeutic application of anti-PLAC1 ADC in a xenograft model of human breast cancer. Our findings support the embryonic origin of cancers and highlight the potential therapeutic value of targeting oncofetal antigens in human breast cancer.